A pilot study on corneal Langerhans cells in keratoconus. Issue 2 (April 2018) - Mandathara, Preeji S.; Stapleton, Fiona J.; Kokkinakis, Jim; Willcox, Mark D.P.
Abstract: Purpose: To report the density and morphology of cells that are analogous to corneal Langerhans cells and their associations in keratoconus. Materials and methods: This prospective cross-sectional study included a convenience sample of keratoconus subjects aged between 18-65 years. Corneal topography, assessment of ocular symptoms, tear variables, corneal sensitivity, in-vivo confocal microscopy were performed. The number of Langerhans cells were manually counted and averaged across three central corneal images. Cell morphology was graded on a 0-3 scale, where grade 3 indicates cells with long visible dendrites. Associations of Langerhans cells with other variables were evaluated using Spearman's correlation. Results: Twenty-one keratoconus subjects with a mean age of 43 ± 11 years were included. Eighty-one percent of them were males, 48% had mild keratoconus and 52% were contact lens wearers. Langerhans cells were present in the central cornea in 91% of subjects. Median cell density was 15 cells/mm 2 (IQR: 3-21). Cell morphology of grades 2 or 3 (with short or long dendrites) was seen in 71% of subjects. There was a significant association between Langerhans cell frequency and density with male gender (rho and p-values: -0.669, 0.001 and -0.441, 0.045) and between Langerhans cell density and nerve fibre tortuosity (0.479, 0.028). No significant association observed with age, contact lens wear or ocular symptoms. Conclusion: Langerhans cells were present in a significant number of subjects suggesting the possibility of inflammation in keratoconus. Based on the association of Langerhans cells with nerve parameters, we propose inflammation as the underlying cause for corneal nerve changes in keratoconus.